Implementation of Internship Program in Mbkm Activities at Eight-Semester of English Department University of Pasir Pengaraian - Rahayu, Pipit; Eripuddin, Eripuddin; Juhastri, Azi Nurazima; Ramadhini, Dea; Arrum, Arrum; Ginting, Rezha Mayshara; Julaika, Julaika; Rahayu, Selvi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the implementation of the internship program within the Merdeka Belajar Kampus Merdeka (MBKM) policy at the English Education Study Program of Universitas Pasir Pengaraian, specifically for eighth-semester students. Utilizing a descriptive qualitative approach, data were collected through questionnaires and interviews with participating students. The findings indicate that the majority of students responded positively towards the planning and execution of the internship program, as well as the support received from academic supervisors and partner institutions. Students felt that the internship tasks were relevant to their academic background and contributed to the development of communication, time management, and teamwork skills. However, some students faced challenges in adapting to workplace culture and balancing academic workload with internship responsibilities. This research recommends enhancements in pre-internship preparation, more consistent supervision, and clearer communication regarding MBKM objectives to improve future internship experiences. Thus, the internship program is expected to be more effective in preparing students to meet the increasingly complex demands of the workforce.